2020
DOI: 10.1136/bmj.m1728
|View full text |Cite
|
Sign up to set email alerts
|

Reducing risks from coronavirus transmission in the home—the role of viral load

Abstract: Paul Little and colleagues call for better promotion of simple measures that can help reduce the spread and severity of infection among those living with people who have covid-19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 18 publications
1
43
1
Order By: Relevance
“…Although some providers have lived apart from their families, it is recommended that providers continue to stay at home with their families [33][34][35]. This preserves everyone's mental health.…”
Section: Mitigating Risk For Providers' Familiesmentioning
confidence: 99%
“…Although some providers have lived apart from their families, it is recommended that providers continue to stay at home with their families [33][34][35]. This preserves everyone's mental health.…”
Section: Mitigating Risk For Providers' Familiesmentioning
confidence: 99%
“…For instance, a rapid dissemination of the infection in care homes would potentially overwhelm medical assistance. And furthermore, repeat and constant exposure to circulating virus occurring in enclosed environments increases the viral load, whichhas, on its part, been associated with more severe COVID-19 and worse clinical outcomes[11,12].…”
mentioning
confidence: 99%
“…In February, a team of World Health Organization (WHO) researchers led by David Heymann investigated the outbreak in Wuhan, China, and concluded that the large majority of transmission events occurred within indoor clusters 24 between family members (accounting for 75%-85% of estimated infections) and coworkers, with no identified cases of child-to-adult transmission identified. 15 In addition, some data suggest that severity of outcomes is associated with initial exposure It may be that advanced age alone, in the absence of preexisting conditions, is less of an independent risk factor than has been assumed.…”
Section: Clear Evidence-based Information Is Often Lackingmentioning
confidence: 99%
“…viral-load levels. [24][25][26] Moreover, it increasingly appears that infection risk from contaminated surfaces has been at least somewhat overstated, as the CDC recently acknowledged. 27 Indeed, it is conceivable that future science historians may conclude that many current COVID-19 prevention strategies had little if any impact, particularly because they targeted drivers of spread accounting for no more than a small proportion of total infections.…”
Section: Clear Evidence-based Information Is Often Lackingmentioning
confidence: 99%